Comparison of Fitness Cost, Stability, and Conjugation Frequencies of tet(X4)-Positive Plasmids in Chicken and Pig Escherichia coli - Ziyi Liu; Huiru Zhang; Xia Xiao; Yuan Liu; Ruichao Li; Zhiqiang Wang (MDPI AG, 2022)
The large-scale epidemic of the tet(X4) gene in the livestock and poultry industry is threatening public health; however, there is still a lack of comparative studies on tet(X4)-bearing plasmids in chicken and pig Escherichia coli. To evaluate the prevalence trend of tet(X4)-bearing plasmids and the factors influencing their persistence in the livestock and poultry industry, we examined the fitness cost, stability under tetracyclines pressure, and conjugation frequencies at various temperatures of six tet(X4)-bearing plasmids in four representative pig E. coli isolates and chicken E. coli isolates. Compared with pig E. coli, the plasmid in chicken E. coli showed lower fitness cost, and stronger ability to promote bacterial biofilm formation and motility. Meanwhile, the presence of tetracycline may favor the stability of tet(X4)-bearing plasmids, which was more common in chicken E. coli. Furthermore, the optimal temperature for IncX1 tet(X4)-bearing plasmid conjugation was 42 °C, and its conjugation frequency in chicken E. coli was higher than that in pig E. coli, whereas the optimal temperature for IncFII tet(X4)-bearing plasmid conjugation was 37 °C and it performed better in pig E. coli, suggesting the predominant plasmid types circulating in chicken E. coli and pig E. coli may be distinct. Collectively, although tet(X4) currently appears to be more prevalent in pig E. coli, this is probably independent of the fitness cost caused by tet(X4)-plasmids. To curb the future spread of the tet(X4) gene, reduced tetracyclines usage and tailored interventions should be applied in different breeding industries.